Efeitos dos resíduos de beneficiamento do café e do granito na fertilidade do solo e no desenvolvimento do milho (Zea mays L.) - Campos, Luana Morati (2018)
The sectors for the processing of ornamental stones and coffee are relevant to the economy of Espírito Santo. However, such industrial activities produce tons of waste daily and their reuse is a way to promote the sustainability of productive processes. The use of these residues in agriculture as sources of nutrients for plants is a process that requires studies that identify their influence on plant growth and soil attributes. Thus, this work is the product of three experiments, whose objectives were: 1) To evaluate the growth of maize plants (Zea mays L.) and leaf chlorophyll index, as well as soil fertility, due to application of increasing doses of granite processing waste obtained in multi wire saw and two liming levels; 2) To determine the growth and nutrient content in the aerial parts of maize plants, as well as the soil fertility, in function of increasing doses of the mix of dry sludge and ash from the industrial processes of soluble coffee and two liming levels; 3) To establish growth, foliar and root anatomy, photosynthesis, chlorophyll fluorescence, leaf chlorophyll and total carotenoid content, soluble carbohydrate content and nutrient concentration of aerial parts of maize plants, as well as determine the soil fertility characteristics due to the application of a dose of granite processing waste obtained in multi wire saw and the use of a dose of the mix of dry sludge and ash from industrial processes of soluble coffee with and without lime. The results show that both residues used in the experiments, without or with lime, can generally increase the values of the analyzed variables. In experiments 1 and 2, the application of increasing doses of the granite and coffee processing waste induced an increase on soil pH and a reduction on potential acidity (H+Al). In addition, the residues increased the sum of bases and soil nutrient contents, such as calcium, magnesium, manganese and copper. However, in the case of the application of granite processing waste, this provided an excessive increase of copper in the soil. The lime increased soil pH and reduced H+Al. Besides that, higher height, stem diameter and biomass occurred in relation to the control treatments. However, the copper content of granite processing waste and the caffeine of coffee processing waste may have made it impossible to increase these parameters. In the experiment 3, the treatments with granite processing waste plus simple superphosphate (SS) increased the phosphorus concentration in the soil in relation to the other treatments, while the treatments with coffee processing waste increased the contents of potassium, calcium and manganese in relation to the other treatments. The use of granite processing waste plus SS provided, as a rule, higher growth and nutrient content by mass of dry matter of the aerial part per vessel when compared to the use of coffee processing waste, which, in turn, provided higher values of these parameters in relation to non-application of waste. The addition of lime tended to increase the values of sum of bases, cation exchange capacity and base saturation, as well as some nutrients, in relation to the non-addition of lime. In addition, liming tended to increase pH and reduce H+Al, but in small magnitude. Generally, the application of both residues allowed the increment of the anatomical variables, of gas exchanges, chlorophyll a fluorescence, chlorophyll a content and total soluble carbohydrates when compared to non-application of residues. The granite processing waste of diamond multi wire saw plus SS can be used at a dose of 10 t ha-1 per application and the coffee processing waste can be used at 29 t ha-1 , favoring the adequate initial growth of the maize plants, however, in greater evidence in the case of the use of the granite processing waste plus simple SS. Therefore, it can be affirmed that the agricultural use of these materials is an ecologically correct and economically viable option, which provides benefits to all parties involved in its generation and disposal.